The Modulation of Cholesterol Metabolism Is Involved in the Antiviral Effect of Nitazoxanide - Claudio Fenizia; Salomè Valentina Ibba; Claudia Vanetti; Sergio Strizzi; Jean-François Rossignol; Mara Biasin; Daria Trabattoni; Mario Clerici (MDPI AG, 2021)
We previously investigated the role of Nitazoxanide (NTZ), a thiazolide endowed with antiviral and antiparasitic activity, in HIV-1 infection. NTZ treatment in primary isolated PBMCs was able to reduce HIV-1 infection in vitro by inducing the expression of a number of type-I interferon-stimulated genes. Among them, NTZ was able to induce cholesterol-25-hydroxylase (CH25H), which is involved in cholesterol metabolism. In the present study, we wanted to deepen our knowledge about the antiviral mechanism of action of NTZ. Indeed, by inducing CH25H, which catalyzes the formation of 25-hydroxycholesterol from cholesterol, NTZ treatment repressed cholesterol biosynthetic pathways and promoted cholesterol mobilization and efflux from the cell. Such effects were even more pronounced upon stimulation with FLU antigens in combination. It is already well known how lipid metabolism and virus replication are tightly interconnected; thus, it is not surprising that the antiviral immune response employs genes related to cholesterol metabolism. Indeed, NTZ was able to modulate cholesterol metabolism in vitro and, by doing so, enhance the antiviral response. These results give us the chance to speculate about the suitability of NTZ as adjuvant for induction of specific natural immunity. Moreover, the putative application of NTZ to alimentary-related diseases should be investigated.